Enhancing Disaster Mitigation Efforts Through Community Engagement at Lampuyang Public Elementary School, Pulo Aceh - As – Syifayatul Amalia; Rahmah Ulfa; Nurul Kamaly; Nofriadi; Ismatur Rahmi; Zulfa Harirah (Dedikasi Sosial: Jurnal Pengabdian Masyarakat, 2025)
Pulo Aceh is highly vulnerable to natural disasters, including earthquakes and tsunamis. The lack of awareness and limited knowledge among the community, particularly elementary school students, regarding disaster mitigation efforts poses a serious challenge in fostering local community resilience. This community service activity aims to enhance students' disaster awareness and preparedness at Lampuyang. Public Elementary School, Pulo Aceh. The methods used include interactive education, evacuation simulations, and emergency response training tailored to local conditions and participant age. The results show an increase in students' understanding of types of disasters, initial self-rescue steps, and the importance of individual and school preparedness in facing emergencies. Strengthening disaster mitigation capacity at the elementary school level has proven effective as an initial strategy for cultivating a disaster-aware culture from an early age. This activity is expected to serve as a model for school-based disaster education that can be implemented in other disaster-prone areas.